Legal Analysis of the Establishment of a Sole Proprietorship Based on PP No. 8 of 2021 - Esekiel Tarigan; Widodo Ramadhana; Dody Ariyanto (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
The government formed a draft law on job creation which aims to facilitate the business climate in Indonesia. This bill is included in the 2020 Prolegnas priority list and is expected to increase Indonesia's ease of doing business ranking in the world, especially related to indicators of starting a business which lags behind neighboring countries and ranks fifth at the ASEAN level. For this reason, the Government has created a breakthrough so that everyone can easily start a business, especially for Micro and Small Enterprises (UMK). A number of clusters of Draft Laws have been prepared and one of these sub-clusters is related to the formation of business entities. In order to realize the ease of doing business, there is a need to form a new type of business entity, especially for Micro and Small Enterprises in the form of a Limited Liability Company (PT) which was established by one person. Individual Limited Liability Companies are expected to provide convenience for Micro and Small Business actors in forming companies with minimum requirements and capital. By using the normative juridical method, this article discusses the concept of an individual limited liability company by comparing the arrangements with other countries so that it can be a lesson for Indonesia if it wants to make this happen. From the results of the study, appropriate and comprehensive arrangements are needed in order to realize a Limited Liability Company for Micro and Small Businesses in order to support the ease of doing business in Indonesia.